Analysis of the influence of social and economic dimensions on sustainable development through environmental performance as a mediating variable: A structural equation modeling-partial least squares approach - Almira Cindy Khaerunisa (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2026)
Background: Sustainable development demands a balance between social, economic, and environmental dimensions. This study aims to analyze the influence of social and economic dimensions on sustainable development with environmental performance as a mediating variable using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. Methods: This study uses secondary data from the Indonesian Sustainable Development Indicators (SDGs) report Volume 8 for 2023. The research variables consist of economic, social, environmental, and sustainable development dimensions which are analyzed using SmartPLS 4.0 software to assess validity, reliability, and relationships between constructs. Findings: The results show that economic variables have a significant negative effect on sustainable development (β = −0.930; p = 0.000), while social variables have a positive effect (β = 0.188; p = 0.093). Social variables significantly influence environmental performance (β = 0.516; p = 0.008), whereas economic and environmental variables do not significantly affect sustainability. The model shows strong explanatory power for sustainable development (R² = 0.848) but weak for environmental performance (R² = 0.265). Conclusion: The results show that the economic dimension has a significant negative effect on sustainable development, while the social dimension has a positive but insignificant effect. Environmental performance does not mediate the relationship between social and economic factors on sustainable development. However, the high R² value indicates that the model has strong explanatory power. Sustainable development in Indonesia is still dominated by economic factors, while social and environmental aspects have not provided optimal contributions. Novelty/Originality of this article: This research's novelty lies in the use of Indonesia's 2023 SDGs indicator data using the SEM-PLS approach to test the role of environmental performance as a mediating variable. The results provide a new empirical perspective on the imbalance of sustainable development pillars in developing countries.